Bink & Gollie : Bink & Gollie #1 - DiCamillo, Kate; McGhee, Alison, 1960-; Fucile, Tony (Somerville, Mass. : Candlewick Press, 2010)
Two roller-skating best friends--one tiny, one tall--share three comical adventures involving outrageously bright socks, an impromptu trek to the Andes, and a most unlikely marvelous companion.
Keywords: Friendship -- Fiction; Friendship -- Fiction; Humorous fiction